The burden of norovirus gastroenteritis: an important foodborne and healthcare‐related infection. (August 2014) - Belliot, G.; Lopman, B. A.; Ambert‐Balay, K.; Pothier, P.
Abstract Human norovirus (NoV) is now recognized as one of the most important causative agents of gastroenteritis in all age groups worldwide. During the course of NoV infection, symptoms are usually mild and disappear within 48 h after onset. The incidence of NoV infection is high, with hundreds of cases per 10 000 of the population, although the number of infections is still underestimated. Epidemiological surveys conducted in Europe and North America have shown that NoV infections constitute a major disease burden, especially for young children and the elderly, in whom NoV infection leads to high rates of hospitalization and mortality. NoV infections are also of concern in hospitals, where viral infections can be persistent in immunocompromised patients. Although the cost of NoV infection in the hospital community has not yet been clearly established, it appears that NoV infections could cost hundreds of thousands of euros in terms of unit closure, and NoV‐related sickness in patients and health workers. Besides their clinical burden, NoVs, as foodborne pathogens, also cause to millions of dollars of losses for the healthcare system and the food industry. Recent estimates in the USA showed that, annually, NoV illness cost 2 billion and led to a loss of approximately 5000 quality‐adjusted life‐years, making NoV one of the top five pathogens causing enteric illnesses. The highest cost among 14 foodborne pathogens is also attributed to human NoV in The Netherlands. This accumulation of evidence underlines the enormous impact of NoV on populations.